Testing the Effect of a Cohort Grouping Model as a Form of Instructional Grouping in Teacher Education - Dyson, Lily; Hanley, Betty (Canadian Journal of Higher Education, 2002)
The study examined the effect of cohort grouping as a form of delivering teacher education programs on student social adjustment and acadmic performance. A sample of 94 students entering a Canadian Faculty of Education was divided into two groups: the cohort (n = 46) and the non-cohort group (n = 48). The former shared five courses and learned together from the same instructors for the academic year, and the latter took courses individually. The results showed that while there were no group differences on the measures of social support, self-efficacy, and university adjustment, the non-cohort group made greater gains than the cohort group in the academic performance as measured by the grade point average (GPA) over the academic year.